Age-Related Macular Degeneration in Ethnically Diverse Australia: Melbourne Collaborative Cohort Study. (17th March 2015) - Robman, Liubov D.; Islam, Fakir M. A.; Chong, Elaine W. T.; Adams, Madeleine K. M.; Simpson, Julie A.; Aung, Khin Zaw; Makeyeva, Galina A.; Hopper, John L.; English, Dallas R.; Giles, Graham G.; Baird, Paul N.; Guymer, Robyn H.
Abstract: Purpose : To determine and compare the prevalence of age-related macular degeneration (AMD) in older Australians of Anglo-Celtic and Southern European origin. Methods : A total of 21, 132 participants of the Melbourne Collaborative Cohort Study, aged 47–86 years, were assessed for AMD in 2003–2007 with non-mydriatic fundus photography. Of these, 14% were born in Southern Europe (Greece, Italy or Malta), with the remaining 86% of Anglo-Celtic origin, born in Australia, the United Kingdom or New Zealand. Results : Overall, 2694 participants (12.7%) had early stages of AMD, defined as either one or more drusen ≥125 μm (with or without pigmentary abnormalities) or one or more drusen 63–124 μm with pigmentary abnormalities in a 6000-μm diameter grading grid, in the absence of late AMD in either eye. A total of 122 participants (0.6%) had late AMD, defined as either geographic atrophy or neovascular AMD. In logistic regression analysis, adjusted for age, sex, smoking, education and physical activity, Southern Europeans compared to Anglo-Celts had a higher prevalence of the early stages of AMD (odds ratio, OR, 1.15, 95% confidence interval, CI, 1.00–1.34), and lower prevalence of late AMD (OR 0.36, 95% CI 0.17–0.78). Conclusions : Australians of Southern European origin have a higher prevalence of the early stages of AMD and lower prevalence of late AMD compared to those of Anglo-Celtic origin. Although AMD prevalence in the older age group(s) of Southern Europeans could be underestimated due to disparity in participation rates, it is likely that both lifestyle and genetic factors play their parts in differential AMD prevalence in these ethnic groups.